2003
DOI: 10.1023/b:ajcp.0000004743.37592.26
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cultural and Racial Identification on the Psychosocial Adjustment of Inner‐City African American Children in School

Abstract: The purpose of this study was to examine the relationship and combined influence of racial identity and Africentric values on African American children's psychosocial adjustment. Participants were 104 (53 males, 51 females) African American fourth-grade students attending an inner-city public school in a northeastern city. Child and teacher ratings were used to assess the relationship between racial identity, Africentric values, and several indices of child psychosocial adjustment, including child behavior con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 42 publications
2
52
0
Order By: Relevance
“…This finding proved consistent with results by Stevenson (1997) that showed that African American male youth who held racial socialization beliefs characterized by cultural legacy appreciation were better able to refrain from acting out with defiance and hostility in school than were those without this distinguishing characteristic. This finding is also in accordance with Thomas et al (2003), who showed a significant positive association between teachers' ratings of classroom rule compliance and students' endorsement of traditional cultural values that included knowledge of one's cultural heritage among a younger sample of urban African American students.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding proved consistent with results by Stevenson (1997) that showed that African American male youth who held racial socialization beliefs characterized by cultural legacy appreciation were better able to refrain from acting out with defiance and hostility in school than were those without this distinguishing characteristic. This finding is also in accordance with Thomas et al (2003), who showed a significant positive association between teachers' ratings of classroom rule compliance and students' endorsement of traditional cultural values that included knowledge of one's cultural heritage among a younger sample of urban African American students.…”
Section: Discussionsupporting
confidence: 89%
“…This finding suggests that the more the youth were told about their cultural heritage from parents and other relevant adults in their lives, and presumably internalized these messages, the less likely they were to react to situations and engage in behaviors in the classroom that would put them at risk for negative evaluations of their behavior. Hence, as previously suggested from earlier research (McHale et al, 2006;Stevenson et al, 2002;Thomas et al, 2003), having knowledge of African American history and culture may be an important protective factor for African American youth, providing those students with heritage knowledge more opportunities than others to benefit emotionally and have more successes in social situations at school.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Thomas, Townsend and Belgrave (2003) identify numerous studies with findings indicating that students who experience racial socialization at home have a strong sense of self-identity and identification with their own ethnic group, and experience better psychosocial outcomes as well (Neblett et al, 2009). Racial socialization messages have also been found to lead to better attitudes toward school (Thomas et al, 2003).…”
Section: African American Valuesmentioning
confidence: 91%
“…Moreover, some researchers have examined the African American family context and gleaned that for some families, there exists an Africentric Worldview, "a set of beliefs values and assumptions that reflect basic African values found among persons of African descent including African Americans" (Belgrave, Townsend, Cherry, & Cunningham, 1997, p. 423). The Africentric values include: spirituality, harmony, movement expressiveness, verve, affect, communalism, expressive individualism, morality, and a social time perspective (Belgrave et al, 1997;Boykin, Tyler, Watkins-Lewis, & Kizzie, 2006;Thomas, Townsend, & Belgrave, 2003). These ideals are not often embraced in the school context, which could influence the difficulty that some minority students have navigating between home and school.…”
Section: African American Valuesmentioning
confidence: 99%